Expansion and fragmentation : internationalization, political change, and the transformation of the nation state - Kersbergen, Kees van, 1958-; Lieshout, R. H.; Lock, Grahame, 1946- (Amsterdam University Press, 1999)
An analysis of the significance of the state in the face of progressive internationalization.